2016
DOI: 10.1017/s1041610216000429
|View full text |Cite
|
Sign up to set email alerts
|

Regional functional synchronizations in dementia with Lewy bodies and Alzheimer's disease

Abstract: Background:Dementia with Lewy bodies (DLB) is a common cause of dementia in the elderly population after Alzheimer's disease (AD), and at early stages differential diagnosis between DLB and AD might be difficult due to their symptomatic overlap, e.g. cognitive and memory impairments. We aimed to investigate functional brain differences between both diseases in patients recently diagnosed.Methods:We investigated regional functional synchronizations using regional homogeneity (ReHo) in patients clinically diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…The right motor network showed large clusters of decreased connectivity in DLB within primary motor areas. Sensorimotor networks have been commonly shown to be altered in Lewy body diseases (Tessitore, Giordano, de Micco, Russo, & Tedeschi, ; Wu et al, ; Yu, Liu, Wang, Chen, & Liu, ) and lower connectivity within the motor cortex has been reported previously in DLB (Peraza et al, ; Taylor, Colloby, McKeith, & O'Brien, ). In addition to reduced connectivity within the motor network itself we found that cognitive control areas, such as frontal and default mode areas, were less strongly involved in this network in DLB, which might be related to impairments of voluntary movement control in this disease group.…”
Section: Discussionmentioning
confidence: 84%
“…The right motor network showed large clusters of decreased connectivity in DLB within primary motor areas. Sensorimotor networks have been commonly shown to be altered in Lewy body diseases (Tessitore, Giordano, de Micco, Russo, & Tedeschi, ; Wu et al, ; Yu, Liu, Wang, Chen, & Liu, ) and lower connectivity within the motor cortex has been reported previously in DLB (Peraza et al, ; Taylor, Colloby, McKeith, & O'Brien, ). In addition to reduced connectivity within the motor network itself we found that cognitive control areas, such as frontal and default mode areas, were less strongly involved in this network in DLB, which might be related to impairments of voluntary movement control in this disease group.…”
Section: Discussionmentioning
confidence: 84%
“…These findings could be part of the pathology or alternatively, the result of a compensation mechanism that may occur at early stages of AD. At rest, early stage AD patients may have increased activity and functional connectivity in resting state networks which correlate with a lower MMSE score ( Peraza et al, 2016 ). However, at more advanced stages activity and connectivity decrease to levels lower than those seen in controls ( Agosta et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pathogenesis of AD is associated with aberrantly increased excitatory transmission and calcium degranulation [101]. Neurodegeneration with defects in the gene encoding IGF-1, IGF-2 and their receptors were observed in AD patients after postmortem examination [102]. Neuronal functions like central and peripheral brain functions are insulin dependent and regulate vasodilatation and vasoconstriction via the PI3K → Akt pathway and MAPK → ET, respectively [100].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…Receptor-mediated vasodilatation through PI3K → Akt by nitric oxide synthase results in the production of nitric oxide and vascular relaxation [100]. In diabetic patients, there is reduced vasodilatation due to aberrant insulin signaling which reduces nitric oxide production and cerebral blood flow resulting in dysfunctional neurons and AD progression [102]. Diabetes affects neuropathological mechanisms in the brain by epigenetic modifications which result in increased susceptibility to insults associated with neurodegenerative impairment [104, 105].…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%